NatD promotes glioblastoma progression through epigenetic activation of FGFR4 signalling - Chan-Woo Kim; Taek-Yeol Jung; Chanil Kim; EungHan Kim; Heui Og Kim; Jiyeon Chae; Hyelee Kim; Ga-Yeon Ko; You-Jung Yeo; Ji-Young Park; Jaehyuk Pyo; Jeong Taeg Seo; et al. (Experimental & Molecular Medicine, 2026)
Abstract N-terminal acetyltransferase D (NatD) acetylates histones H4 and H2A at serine 1 and has been implicated in oncogenesis, yet its role in glioblastoma (GBM) remains unexplored. Here, we show that NatD expression is significantly elevated in GBM at both transcript and protein levels. NatD knockdown markedly suppressed proliferation, colony formation, migration, invasion and tumoursphere formation in GBM cell lines and patient-derived models, indicating a critical role in maintaining cancer stem-like properties. These inhibitory effects were rescued by reintroduction of wild-type NatD but not by a catalytically inactive mutant, confirming dependence on its enzymatic activity. Transcriptomic profiling identified fibroblast growth factor receptor (FGFR) 4 as a key downstream effector. Mechanistically, NatD maintained N-terminal acetylation of histones H4 and H2A at the FGFR4 promoter, thereby antagonizing casein kinase 2α-mediated phosphorylation and sustaining an open chromatin state permissive for transcription. NatD depletion reduced FGFR4 expression and downstream ERK1/2 and AKT phosphorylation, whereas FGFR4 overexpression restored malignant phenotypes suppressed by NatD knockdown both in vitro and in xenograft models. Orthotopic xenograft models further demonstrated that NatD depletion suppresses intracranial tumour growth and prolongs survival, whereas FGFR4 re-expression partially restores tumour progression. Analysis of TCGA GBM datasets revealed that the positive correlation between NatD and FGFR4 expression is maintained across multiple molecular subtypes. Collectively, these findings identify NatD as an oncogenic regulator of GBM and underscore NatD–FGFR4 signalling as a promising therapeutic target.